Good Agricultural Practices (GAP) Determinants Among Smallholder Vegetable Farmers: The Case of Majayjay, Laguna, Philippines - Mora, Jennica Amielle; Bonalos, Cris Edwin; Aquino, Eliza (Sharia Agribusiness Journal, 2025)
ABSTRACT Good Agricultural Practices (GAP) are critical for ensuring food safety, environmental sustainability, and access to competitive markets, but adoption among smallholder farmers in the Philippines remains low. This study assessed the determinants of GAP adoption among smallholder vegetable farmers in Majayjay, Laguna. Survey data from 69 farmers were selected through purposive sampling and analyzed using descriptive statistics and Pearson’s chi-square test, and Cramer’s V to examine the relationship between adoption and three variables: membership in farmers’ organization, awareness on GAP, and communication with agricultural extension workers. Results showed that awareness on GAP and communication with agricultural extension workers were significantly associated with adoption, whereas membership in farmers’ organizations was not. These findings highlight the importance of awareness and extension services as key drivers of the respondents’ GAP adoption. While membership in farmers’ organizations may not be significant, strengthening the role of farmers’ organizations can provide institutional and government support and market opportunities that help sustain adoption. This study recommends targeted awareness campaigns, enhanced extension services, and empowered farmers’ organizations to promote GAP adoption among smallholder vegetable farmers. Keywords: good agricultural practices (gap); smallholder vegetable farmers; adoption determinants; agricultural extension; farmer organizations.